Effects of total ghcosides of peony on serum inflammatory factor in type 2 diabetic kidney disease - QI Xiang-ming; ZHU Qi-jin; WU Yong-gui (Linchuang shenzangbing zazhi)
Objective To observe the effects of total glycosides of peony(TGP) on serum hypersensitive C-reactive protein(hs-CRP),monocyte chemotactic protein-1(MCP-1),tumor necrosis factors α(TNF-α) and urinary albumin excretion rate(UAER) in patients with type 2 diabetic kidney disease(DKD) who had microalbumin in urine.Methods Seventy-eight patients with T2 DKD whose UAER was 20-200 g/min were enrolled in this study.They were randomly divided into two groups:TGP group(n= 40,compound TGP capsules plus losartan group,TGP 1 800 mg/day for 6 months),and losartan group(n = 38,treated with losartan 100 mg/day for 6 months).At the end-point,serum hs-CRP,MCP-1 and TNF-α levels were determined by ELISA before and after treatment,and UAER,fasting blood glucose and serum creatinine and lipid profiles were examined.Results At the treatment end-point,UAER was dramaticly decreased in TGP group as compared with that of baseline[(132.58±32.42) mg/24 h vs(56.87±11.71) mg/24 h,t= 13.88,F<0.01],and the percentage of the decrease was 57.1%.UAER in losartan group was significantly decreased as compared with that before treatment[(138.4 ± 38.64) g/24 h vs(104.22 ± 34.24)g/24 h,t = 4.08,P<0.051,and the percentage of the decrease was 24.7%.But the percentage of the decrease was significantly lower in losartan group than that in TGP group.There was no significant difference in serum creatinine level between the TGP and losartan groups in the follow-up end.The levels of hs-CRP,MCP-1 and TNF-αwere significantly lower in both groups after treatment than those before treatment(P<0.01).After treatment,the serum hs-CRP,MCP-1 and TNF-α levels in TGP-treated group were more noticeably reduced than those in the losartan group.No statistical difference in side effects was observed between the two groups.Additionally,there was a positive correlation between UAER and hs-CRP,MCP-1,TNF-α,respectively.Conclusions TGP could retard the development of early DKD through decreasing the production of inflammatory cytokins and inhibiting inflammatory reaction.